Fighting obesity with social marketing - a case study - McAuley, Andrew (Henry Stewart Talks, 2018)
This case study reviews the growing global obesity epidemic and outlines how countries are beginning to confront the problem through a range of social marketing practices. For example, awareness campaigns, re-branding of healthy food and new comprehensive government- and community-led approaches have contributed to tackling the problem.
Archived at 2023/06/22